The Effect of Service Quality and Facilities on Hospitalization Patient Satisfaction Hasanuddin Damrah Manna Hospital - Mohammad Ansyori; Ahmad Soleh; M. Rahman Febliansyah (UNIVED Press, 2024)
Health problems have become a basic need for society. With the increase in people's living standards, the demand for quality health is also increasing. The purpose of this study was to determine the effect of service quality and facilities on inpatient satisfaction at Hasanuddin Damrah Manna Hospital. This study focuses on the effect of service quality and facilities on inpatient satisfaction at Hasanuddin Damrah Manna Hospital. This study used a quantitative research approach, data collection used research instruments, data analysis was statistical with the aim of testing the hypotheses that had been set. Based on the characteristics of the research, a sample of 89 people was obtained. The results of this study indicate that service quality has a significant positive effect on the inpatient satisfaction at Hasanuddin Damrah Manna Hospital. Judging from the results of the t test for the variable quality of service (X1) on patient satisfaction (Y) shows that tcount is greater than ttable (0.000 > 0.05). Facilities have a significant positive effect on inpatient satisfaction at Hasanuddin Damrah Manna Hospital. The Facility variable (X2) on patient satisfaction (Y) tcount is greater than ttable (0.000 > 0.05). The quality of services and facilities simultaneously influence the satisfaction of inpatients at Hasanuddin Damrah Manna Hospital. That the value of Fcount> Ftable, namely 925,583> 3.104.